Effect of Polyurea Coating on Corrosion Resistance Over Mild Steel and Aluminium Substrates for Liquid Storage Applications. (24th July 2018) - Arunkumar, T.; Sunitha, S.; Theerthagiri, J.; Jeevagan, Jaya; Anish, M.; Tatarchuk, Tetiana
Abstract: In response to the extensive demands on national and global levels, liquid storage tanks are designed by circumventing environmental pollution. The storage tanks are metallic containersused to store various liquids and chemicals, such as oil, diesel, biodiesel, liquid fertilizer, industrial chemicals, petroleum products etc. The service life of such storage tanks is usually reduced due to corrosion, and one of the effective means of combating corrosion is to use protective coatings on the metal surface.In this study, the effects of polyurea (PU) coating on corrosion behaviour over aluminium and mild steel substrateswere investigated. Spray coating technique is used for coating. Pure substrates and coated substrates (unscribed and scribed) are prepared and the corrosion behaviour of PU coated samplesare studied with the help of salt spray test and polarization measurements. The results are recorded and discussed. Furthermore, surface morphology and elemental analysis were studied through scanning electron microscopy (SEM) and energy dispersive X-ray analysis (EDAX) respectively.